The Rationale for Higher Education Investment in Ibero-America - Brunner, José Joaquín (OECD Development Centre Working Papers, 2013)
A key higher education policy question is about the financing of this sector. Who, why and how higher education should be paid for are debated around the world by governments, the academic community, students, experts and civil society. This is true of Ibero-America. The meetings of their heads of state or governments have, on various occasions, pronounced on this issue. And within the institutions themselves and on the streets of the principal cities in the region, students and professors have voiced their demands for greater funding. This document advocates the need for shared higher education funding - between the state and the private sector, (including students and their families), in a proportion that corresponds approximately to the private and social benefits generated. The proposed public/private cost allocation (1:1) is based on econometric calculations of the respective benefits generated by tertiary education, with approximately one half of the total being private benefits and the other half social benefits and public externalities. From this it follows that HEIs should be funded in the same proportion, diversifying their sources so that the state (taxpayers) and the private sector (households or families, students and graduates) provide 50% each. But the above only makes sense if higher education can ensure that it provides the anticipated private and social benefits and public externalities. The bottlenecks that stand in the way of achieving these expectations have to be removed. So the State should allocate resources in terms of reaching these objectives, and implement policies that encourage institutions to reach the proposed outcomes and standards